Impact of 3D Printouts in Optimizing Surgical Results for Complex Congenital Heart Disease. Issue 5 (September 2019) - Han, Frank; Co-Vu, Jennifer; Lopez-Colon, Dalia; Forder, John; Bleiweis, Mark; Reyes, Karl; DeGroff, Curt; Chandran, Arun
Planning corrective and palliative surgery for patients who have complex congenital heart disease often relies on the assessment of cardiac anatomy using two-dimensional noninvasive cardiac imaging modalities (echocardiography, cardiac magnetic resonance imaging, and computed tomography scan). Advances in cardiac noninvasive imaging now include the use of three-dimensional (3D) reconstruction tools that produce 3D images and 3D printouts. There is scant evidence available in the literature as to what effect the availability of 3D printouts of complex congenital heart defects has on surgical outcomes. Surgical outcomes of study subjects with a 3D cardiac printout available and their paired control subject without a 3D cardiac printout available were compared. We found a trend toward shorter surgical times in the study group who had the benefit of 3D models, but no statistical significance was found for bypass time, cross-clamp time, total time, length of stay, or respiratory support. These preliminary results support the proposal that 3D modeling be made readily available to congenital cardiac surgery teams, for use in patients with the most complex congenital heart disease.